Love Styles and Relationship to Personality Dimensions (Damascus University Journal of educational and Psychologyical sciences, 2022)
The current study aims to find out the relationship between methods of love as defined by Lee and Eysenck’s personality dimensions on a sample of students from the University of Kalamoon (200 male and 200 female students). The researcher used the Hendrick et al scale and EPQ. The most important results of the study are: extraversion correlates with the two styles (Eros, Ludus), neuroticism correlates with the mania style and negatively with the pragma style, and the negative correlation of psychoticism with the (Storge, agape). There were differences in Eros and Ludus in favor of males and mania, agape and neuroticism in favor of females; however, there were no differences between males and females in pragma, storge, extraversion and psychoticism. As for the arrangement of love methods among the sample members, agape was the first for males and mania for females
Keywords: Eros; Ludus; mania. Pragma; Storge; agape; Extraversion; neuroticism; Psychoticism